A Feasibility Study of Caustic Soda (NaOH) Industry with a Capacity of 0,5 MTPY in Gresik as Part of Indonesia's Downstream Industry Program - Oetomo, Dedy Setyo (Journal of Information System, Technology and Engineering, 2026)
Indonesia's dependence on imported caustic soda (NaOH) poses a significant strategic vulnerability, particularly for the textile, paper, alumina refining, and water-treatment industries. This study presents a comprehensive feasibility analysis for establishing a 500,000-ton-per-year NaOH plant in Gresik, East Java, under the Indonesian government's downstream industry (hilirisasi) program. The chlor-alkali membrane electrolysis process was selected as the production method owing to its superior energy efficiency and product purity. Mass and energy balances were rigorously calculated, establishing brine feed requirements of approximately 1,500,000 tons per year and a specific energy consumption of 2,800 kWh per ton of NaOH. Technical process design, equipment sizing, and utility requirements are presented alongside a detailed economic evaluation. Capital expenditure (CAPEX) is estimated at USD 680 million, with an annual operating expenditure (OPEX) of USD 290 million. Financial analysis yields a net present value (NPV) of USD 412 million, an internal rate of return (IRR) of 18.7%, a payback period of 5.4 years, and a break-even point at 62% plant utilization. The Gresik location provides strategic advantages including proximity to raw material sources, existing industrial infrastructure, and deep-water port access. Environmental impact and sustainability assessments confirm compliance with Indonesian environmental standards. This study concludes that the proposed NaOH plant is technically viable and financially attractive, supporting national self-sufficiency in basic chemicals.